Portable Device for Transformer Oil Inhibitor Content Analysis Using Near-Infrared Spectroscopy Wavelength - Leong Y.S.; Jern Ker P.; Hasnul M.H.; Khamis M.A.; Hannan M.A.; Jamaludin M.Z.; Looe H.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric transformer testing; Infrared devices; Mean square error; Near infrared spectroscopy; Power transformers; Voltage measurement; Conventional techniques; Inhibitor concentration; New mathematical model; Optical measuring devices; Performance comparison; Prototype verification; Root mean square errors; Transformer oil samples; Oil filled transformers